Understanding Plastics Recycling : Economic, Ecological, and Technical Aspects of Plastic Waste Handling - Rudolph, Natalie, author 649317; Kiesel, Raphael, author 649319; Aumnate, Chuanchom, author 649320; ScienceDirect (Online service) 7722 (Munich : Hanser, 2017)
Understanding Plastics Recycling shows the true and often-underestimated market potential of plastics recycling, with analysis from economic, ecological, and technical perspectives. It is aimed at both technical and non-technical readers, including decision makers in material suppliers, plastic product manufacturers, governmental agencies, educators, and anyone with a general interest in plastics recycling. An overview of waste handling systems with a focus on the U.S. market is provided. Different methods of waste handling are compared from both economic and ecological perspectives. Since plastic waste recycling is essential from an ecological point of view, common strategies and new approaches to both increase the recycling rate and improve recycling economically and technically are presented. This includes processing and material properties of recycled plastics. Finally, a worldwide outlook of plastic recycling is provided with analysis of additional worldwide markets, encompassing highly developed, fast-developing, and less developed countries.